Electrochemical immunosensor based on antibody-nanoparticle hybrid for specific Detection of the dengue virus NS1 biomarker - Darwish, N.T.; Alrawi, A.H.; Sekaran, S.D.; Alias, Y.; Khor, Sook Mei (Electrochemical Society, 2016)
Dengue virus infection is a very deadly disease that threatens human lives in subtropical and tropical regions. Thus, for early and reliable diagnosis of Dengue virus infection, a sensitive, specific, and label-free electrochemical immunosensor was developed for the direct detection of the unstructured protein NS1. The NS1 biosensor was designed with a biosensing surface consisting of antifouling moieties and biorecognition molecules to enhance the specificity of the immunosensor for target analyte detection in complicated biological samples such as human sera. The immunosensor exhibited a wide detection range (54000 ng/mL) based on electrochemical impedance spectroscopy (EIS) measurements with a coefficient of determination (R2) of 0.94, correlation coefficient (R) of 0.95, high reproducibility, and good stability for 21 days at 4°C. The developed immunosensor was able to detect the NS1 antigen in actual serum specimens from patients infected with Dengue virus. Moreover, the immunosensor is not only highly selective for the NS1 antigen, but also did not cross-react with human sera infected with malaria parasites.